DETERMINANTS OF ADHERENCE TO TREATMENT AMONG HEMODIALYSIS PATIENTS IN MAKKAH CITY, KINGDOM OF SAUDI ARABIA - Ghanim. Hamid. Al-Khattabi (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Background: Adherence of hemodialysis patients to medical instructions is considered crucial for a longer life expectancy and better quality of life. There is solid evidence that non-adherence to end-stage renal disease patients correlates with morbidity and mortality, is the norm for dialysis patients rather than the exception, multiple factors influence it and inconsistencies exist in findings of the relationships between risk factors and non-adherence. Despite the importance of this topic, there is remarkable paucity in the studies which identify factors associated with non-adherence in hemodialysis patients in Saudi Arabia. Aims and Objectives: The current study aims at ameliorating the adverse consequences of non-adherence among hemodialysis patients through providing scientific background and a better understanding of the factors associated with non-adherence. The objectives of this study were to determine factors related to non-adherence to fluid, diet, medication, and hemodialysis sessions among hemodialysis patients in Makkah city. Materials and Methods: The present study is a cross-sectional one, where a sample of 361 hemodialysis patients was selected randomly from hemodialysis centers in three governmental hospitals in Makkah in order to determine factors related to their non-adherence to treatment by using an end-stage renal disease-adherence questionnaire (ESRD-AQ) in addition to clinical examination and laboratory investigation for other data. Results: Younger (<30 years), unmarried, non-Saudis, those with chronic diseases other than hypertension and diabetes mellitus, and those with long dialysis duration (60+ months) were found more likely to be non-adherent to fluid. Females patients and those with short dialysis duration (<60 months) were found more likely to be non-adherent to diet and medications, respectively. Conclusion: Patients who had factors associated with non-adherence deserve special attention and support to improve their adherence behavior. The findings from this study can be used as a base for designing an intervention aimed to increase the adherence to treatment in end-stage renal disease patients who are undergoing hemodialysis in order to decrease the direct and indirect costs that appear as a consequence of non-adherence.